Preliminary study on the value of high-order functional magnetic resonance imaging in the evaluation of bone and soft tissue tumors - ZHANG Zhengjia; LI Xiaomin; ZHOU Xin; MA Hairong; AI Songtao (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To preliminarily investigate the value of high-order functional magnetic resonance imaging in the evaluation of benign and malignant bone and soft tissue tumors and the changes after chemotherapy.Methods·Patients clinically diagnosed with bone and soft tissue tumors at the Department of Orthopaedics, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, from October 2014 to December 2024 were enrolled. The patients were divided into a control group and an amide proton transfer-weighted imaging (APTw) group according to the imaging method. All patients underwent conventional magnetic resonance imaging (MRI), diffusion-weighted imaging (DWI), and dynamic contrast-enhanced imaging (DCE) before surgery. Patients in the APTw group received additional APTw imaging. Both groups were divided into non-malignant and malignant lesion subgroups according to pathological results. According to whether the patients received chemotherapy before enrollment, the patients with malignant lesions in the APTw group were further divided into malignant group without chemotherapy and malignant group with chemotherapy. Clinical and imaging data, including APT values, apparent diffusion coefficient (ADC), and time-intensity curves (TICs) from the largest tumor section, were collected and analyzed to assess the diagnostic performance of APTw, DWI, and DCE, and to evaluate changes after chemotherapy.Results·Eighty-five patients were enrolled, including 51 males and 34 females, with ages ranging from 10 to 84 years, and a mean age of (43.05±17.62) years. There were 51 patients in the control group (16 with non-malignant lesions and 35 with malignant lesions) and 34 patients in the APTw group (5 with non-malignant lesions and 29 with malignant lesions; 23 malignant lesions without chemotherapy and 6 malignant lesions with chemotherapy). The clinical and imaging data showed that only the tumor margin of the control group and the maximum tumor diameter of the APTw group had statistically significant differences in their malignant and non-malignant lesion groups (P<0.05). In the APTw group, there was a statistically significant difference in APT values between the malignant lesion group and the non-malignant lesion group (P<0.001). Further analysis showed that the APT values in the malignant group without chemotherapy were significantly lower than that in the malignant group with chemotherapy (P<0.001). However, there were no statistically significant differences in APT values between the malignant group with chemotherapy and the non-malignant lesion group (P>0.05). There were no significant differences in ADC values and TIC types between malignant and non-malignant lesion groups in the control group and the APTw group (P>0.05). The area under the curve (AUC) of the diagnostic model in the APTw group (MRI+DWI+DCE+APTw) for distinguishing malignant from benign tumors was significantly higher than that of the control group (MRI+DWI+DCE) (P<0.05). The Youden index and specificity of the diagnostic model in the APTw group were higher than those in the control group.Conclusion·As a high-order functional MRI technique, APTw imaging is capable of evaluating the nature (benign or malignant) of bone and soft tissue tumors and detecting changes after chemotherapy. It serves as a valuable supplement to conventional MRI, DWI, and DCE imaging, providing a novel noninvasive tool for the diagnosis and treatment evaluation of bone and soft tissue tumors.